Many Years of Experience - Nunziante Rosania (Critical Hermeneutics, 2024)
In this contribution, the former Director of the last Criminal Asylum to close its doors, gives us a brief overview of his experience. He argues the most significant breakup moments, without forgetting the proposals and suggestions for future improvements. Finally, he gives us an original document, from the V. Madia historical archive. This is a life in the asylum portrait.